Handbook to Stonehenge, the Bermuda Triangle, and other mysterious locations - Omoth, Tyler (North Mankato, Minnesota : Capstone Press, 2017)
Explores mysterious locations around the world and shares theories of scientific explanation as well as paranormal speculation surrounding them.
Includes bibliographical references (page 31) and index.
6.7
3-6
910L
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Haunted places -- Juvenile literature; Curiosities and wonders -- Juvenile literature; Haunted places; Curiosities and wonders